2011
DOI: 10.4103/0976-3147.83586
|View full text |Cite
|
Sign up to set email alerts
|

Unusual features in chronic inflammatory demyelinating polyneuropathy: Good outcome after prolonged ventilatory support

Abstract: Severe respiratory muscle paralysis and ventilatory failure is rare in chronic inflammatory demyelinating polyneuropathy (CIDP). We report a 14 year child who presented with respiratory failure, bulbar and multiple cranial nerves involvement along with bilateral phrenic nerve paralysis. He was diagnosed with CIDP after electrophysiological evaluation. He required AMBU ventilation for about 4 months (including domiciliary use), after which he recovered significantly. Along with several unusual features of CIDP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…However, she developed respiratory insufficiency due to phrenic nerve palsy in the fifth attack and was lost due to sepsis [12]. Jha et al [5] reported a case of a 14-yearold boy who developed bulbar and phrenic nerve palsy following insidiously progressive quadriparesis over 1 yr. The outcome was good after prolonged artificial manual breathing unit ventilation for 4 mo, including domiciliary use [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, she developed respiratory insufficiency due to phrenic nerve palsy in the fifth attack and was lost due to sepsis [12]. Jha et al [5] reported a case of a 14-yearold boy who developed bulbar and phrenic nerve palsy following insidiously progressive quadriparesis over 1 yr. The outcome was good after prolonged artificial manual breathing unit ventilation for 4 mo, including domiciliary use [5].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, few such reported cases were associated with phrenic nerve palsy. Lower cranial nerve palsy is also uncommon (5%) in CIDP [5]. The basis of the flaccid paralysis is conduction block due to demyelination; but axonal connections usually remain intact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Azathioprine is commonly administered when first-line therapy is unsuccessful or when a dose decline of corticosteroids is predicted. The doses of azathioprine consumption in childhood CIDP were 1 mg/ kg/day (in mixture with corticosteroids and IVIG), and 2 -3 mg/kg/day up to 50 -150 mg/day (28,48,58,65). Cyclosporine A inhibited the activation and proliferation of T cell.…”
Section: Immunosuppressive and Cytotoxic Drugsmentioning
confidence: 99%